Electronics and Communication Engineering - Signals and Systems - Discussion

Discussion Forum : Signals and Systems - Section 10 (Q.No. 1)
If F(jω) is the Fourier transform of f(t), then
£ f(- t) = F(jω)
£ f(- t) = F* (jω)
£ f(- t) = F(- jω)
£ f(- t) = F* (- jω)
Answer: Option
No answer description is available. Let's discuss.
1 comments Page 1 of 1.

IJJADA ADINARAYANA said:   9 years ago
What's the difference between options B and C in this regard? What's the right answer?

Post your comments here:

Your comments will be displayed after verification.